2005
DOI: 10.1007/s11010-005-0822-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of radioprotective activities of Rhodiola imbricata Edgew – A high altitude plant

Abstract: The present study reports the radioprotective properties of a hydro-alcoholic rhizome extract of Rhodiola imbricata (code named REC-7004), a plant native to the high-altitude Himalayas. The radioprotective effect, along with its relevant superoxide ion scavenging, metal chelation, antioxidant, anti-lipid peroxidation and anti-hemolytic activities was evaluated under both in vitro and in vivo conditions. Chemical analysis showed the presence of high content of polyphenolics (0.971 +/- 0.01 mg% of quercetin). Ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…Several recent publications report the ability of some herbal constituents to act as radioprotectors (Devipriya et al, 2008;Park et al, 2008;Jagetia and Venkatesha, 2006). Some of the herbal preparations, including Triphala (Jagetia et al, 2002), or Septilin (Jagetia and Baliga, 2004), extracts of Rhodiola imbricata (Arora et al, 2005, Goel et al, 2006, Podophyllum hexandrum (Samanta et al, 2004), Pillea microphilla (Prabhakar et al, 2007), as well as the secondary metabolites such as mangiferin (Jagetia and Baliga, 2005) and naringin (Jagetia et al, 2003) administered to mice intraperitoneally, showed notable protection of normal tissues from irradiation-induced injuries. The present results show that mangiferin can inhibit the irradiationinduced decrease in human PBMC cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent publications report the ability of some herbal constituents to act as radioprotectors (Devipriya et al, 2008;Park et al, 2008;Jagetia and Venkatesha, 2006). Some of the herbal preparations, including Triphala (Jagetia et al, 2002), or Septilin (Jagetia and Baliga, 2004), extracts of Rhodiola imbricata (Arora et al, 2005, Goel et al, 2006, Podophyllum hexandrum (Samanta et al, 2004), Pillea microphilla (Prabhakar et al, 2007), as well as the secondary metabolites such as mangiferin (Jagetia and Baliga, 2005) and naringin (Jagetia et al, 2003) administered to mice intraperitoneally, showed notable protection of normal tissues from irradiation-induced injuries. The present results show that mangiferin can inhibit the irradiationinduced decrease in human PBMC cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, INMAS took the lead in radiation countermeasure development programme and evaluated Indian herbs as the prominent sources of radioprotective molecules. Podophyllum hexandrum, Hippophae rhamnoides, Rhodulla embricata and Tinospora cordifolia was evaluated for their radioprotective efficacy [46][47][48][49][50][51][52] . Apart from that radioprotective efficacy of pure molecules isolated from Podophyllum hexandrum was established at INMAS 53 .…”
Section: Biological Radioprotector Developmentmentioning
confidence: 99%
“…Rhodiola imbricata, a high-altitude plant also rich in antioxidants, exhibits both in vitro and in vivo radioprotection via a superoxide ion scavenging process. [30] Recently, Huang et al [28] found that extracts of the leaves of Nelumbo nucifera Gaertn, because of its antioxidant effects, protects animal models against UVB-induced phototoxicity. Polyphenols (mainly phenols and flavonoids) are the major components of plants that showed antioxidant activity.…”
Section: Viability Of Uv-irradiated Cellsmentioning
confidence: 99%